Strategy To Increase The Competitiveness Of Indonesian Processed Food Products To Thailand Through The Role Of Human Resources Competence: Analysis Of Revealed Comparative Advantage (RCA) And Dynamic Export Competitiveness Index (ECI) - Yasykur Hidayatulloh; Dewi Yustiana; Koen Irianto Uripan; Sutoyo; Sutomo (PT Maju Malaqbi Makkarana, 2026)
This research aims to formulate a strategy to increase the competitiveness of Indonesian food and beverage products in the Thai market through the role of human resource (HR) competencies and participation in international exhibitions. The research approach used is mixed-method, which combines qualitative and quantitative analysis. Qualitative data were collected through in-depth interviews with exporters and related stakeholders, while quantitative data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. In addition, product competitiveness is evaluated through the Revealed Comparative Advantage (RCA) approach and the Dynamic Export Competitiveness Index (ECI) dynamically for the period 2021–2024. The results of the study show that human resource competence has a significant effect on increasing export competitiveness, with a t-statistic value of 5.949 and a p-value of 0.000. The role of international exhibitions has also been proven to indirectly contribute to increasing competitiveness through improving human resource competence. RCA and ECI analysis showed positive trends in several superior products such as processed fish, sauces and spices, as well as margarine and fat mixtures. These findings reinforce the importance of human resource development strategies and the use of international exhibitions as a means of market penetration. This study recommends that governments, stakeholders, and business actors be able to strengthen export-oriented HR training programs and encourage active participation in curated international exhibitions. This research also opens up further study space regarding the integration of digitalization aspects in the promotion of Indonesia's superior products to the global market.